Rifampin Use and Safety in Hospitalized Infants - Arnold, Christopher J. (Am J Perinatol, 2015)
OBJECTIVE: To examine the use and safety of rifampin in hospitalized infants. STUDY DESIGN: Observational study of clinical and laboratory adverse events among infants exposed to rifampin from 348 neonatal intensive care units managed by the Pediatrix Medical Group between 1997 and 2012. RESULT: 2500 infants received 4279 courses of rifampin; mean gestational age was 27 weeks (5(th), 95(th) %tile; 23, 36) and mean birth weight was 1125 g (515, 2830). Thrombocytopenia (121/1000 infant days) and conjugated hyperbilirubinemia (25/1000 infant days) were the most common laboratory adverse events. The most common clinical adverse events were medical necrotizing enterocolitis (64/2500 infants, 3%) and seizure (60/2500 infants, 2%). CONCLUSION: The overall incidence of adverse events among infants receiving rifampin appears low; however, additional studies to further evaluate safety and dosing of rifampin in this population are needed.